2016
DOI: 10.1111/cge.12850
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the proprioception and touch sensation channel PIEZO2 in siblings with a progressive form of contractures

Abstract: Dominant mutations in PIEZO2, which codes for the principal mechanotransduction channel for proprioception and touch sensation, have been found to cause different forms of distal arthrogryposis. Some observations suggest that these dominant mutations induce a gain-of-function effect on the channel. Here, we report a consanguineous family with three siblings who showed short stature, scoliosis, gross motor impairment, and a progressive form of contractures involving the distal joints that is distinct from that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 12 publications
2
41
0
1
Order By: Relevance
“…Additionally, knockout studies in mice show that Piezo2 is critical for many aspects of light touch and proprioception. In agreement with the mouse data, humans carrying non-functional Piezo2 display profound mechanosensory and proprioceptive deficits (Chesler et al, 2016; Delle Vedove et al, 2016; Mahmud et al, 2016). Knockdown experiments also indicate that it may play a role in the development of hyperalgesia.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, knockout studies in mice show that Piezo2 is critical for many aspects of light touch and proprioception. In agreement with the mouse data, humans carrying non-functional Piezo2 display profound mechanosensory and proprioceptive deficits (Chesler et al, 2016; Delle Vedove et al, 2016; Mahmud et al, 2016). Knockdown experiments also indicate that it may play a role in the development of hyperalgesia.…”
Section: Discussionsupporting
confidence: 85%
“…; Mahmud et al. ). In addition to these sensory deficits, mutations in Piezo2 are responsible for complex syndromes that involve joints, ocular muscles and bones (see McMillin et al.…”
Section: Introductionmentioning
confidence: 98%
“…The majority of PIEZO2 dominant mutations are clustered in 2 regions of the gene that encode the C-terminal domain and appear to be mutation hotspots, particularly the last exon 52. In contrast, the mutations in recessive DAIPT do not show any locus predilection, as they are distributed throughout the entire gene [Chesler et al, 2016;Delle Vedove et al, 2016;Haliloglu et al, 2017;Mahmud et al, 2017]. The PIEZO2 protein contains more than 30 transmembrane domains and functions as part of mechanically activated cation channels [Coste et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of sensory and kinematic functions was studied in 2 patients who both carried compound heterozygous mutations in the PIEZO2 gene [Chesler et al, 2016]. Mahmud et al [2017] and Haliloglu et al [2017] reported 4 more patients from 2 families. The heterozygous carriers (parents and siblings) were healthy.…”
mentioning
confidence: 99%